Ultrafast decay dynamics of electronically excited 2-ethylpyrrole. Issue 32 (9th August 2021) - Yuan, Wenpeng; Yang, Dongyuan; Feng, Baihui; Min, Yanjun; Chen, Zhichao; Yu, Shengrui; Wu, Guorong; Yang, Xueming
Abstract : The ultrafast excited-state dynamics of 2-ethylpyrrole is studied in detail using the time-resolved photoelectron imaging method. Abstract : The excited-state decay dynamics of 2-ethylpyrrole following UV excitation in the wavelength range of 254.8–218.0 nm is investigated in detail using the femtosecond time-resolved photoelectron imaging method. The time-resolved photoelectron spectra and photoelectron angular distributions at all pump wavelengths are carefully analysed and the following picture is derived: at the longest pump wavelengths (254.8, 248.3 and 246.1 nm), 2-ethylpyrrole is excited to the S1 ( 1 πσ*) state having a lifetime of about 50 fs. At 248.3, 246.1 and 237.4 nm, another excited state of Rydberg character is excited. The lifetime of this state is ∼570 fs at 237.4 nm and becomes slightly longer at other two pump wavelengths. At the shortest pump wavelengths (230.8 and 218.0 nm), 2-ethylpyrrole is excited to a state which is tentatively assigned to the 1 1 ππ* state, having a lifetime of 75 ± 15 and 48 ± 10 fs for the longer and shorter pump wavelengths, respectively. Internal conversion to the S1 ( 1 πσ*) state might be one of the decay mechanisms of the 1 1 ππ* state.